Subgingival Microbiota Profile in Association with Cigarette Smoking in Young Adults: A Cross-Sectional Study - Krešimir Bašić; Kristina Peroš; Zrinka Bošnjak; Ivana Šutej (MDPI AG, 2021)
While smoking is recognized as one of the factors for the development and progression of periodontal diseases, a relation between the composition of the subgingival microbiota and smoking is yet to be elucidated. The aim of this study was to investigate the prevalence of subgingival bacteria in young smokers and non-smokers without clinical signs of periodontal disease. In this cross-sectional study, performed at the Department of Pharmacology, School of Dental Medicine, University of Zagreb, we enrolled 32 periodontally healthy smokers and 32 non-smokers, aged 25-35 years old. The number of oral bacteria and the prevalence of particular bacteria were assessed for each subject. Subgingival plaque samples were collected with sterile paper points from two first molars for microbiological analyses with MALDI-TOF mass spectrometry. In smokers, a significantly higher prevalence of Actinomyces odontolyticus was observed compared to non-smokers, and a significantly lower prevalence of Streptococcus sanguinis was observed compared to non-smokers. Smoking affects the composition of subgingival microbiota, either via depletion of beneficial bacteria or the increase in pathogenic bacteria.